Meta-analysis of dose selection for budesonide in the treatment of Chinese patients with AECOPD - Mengsha Qi; Runzhong Wang; Shuyun Liu; Fengming Tang (Journal of the Pakistan Medical Association, 2021)
Published in August 2021